2010
DOI: 10.1080/00672700903291765
|View full text |Cite
|
Sign up to set email alerts
|

Kansyore fisher-foragers and transitions to food production in East Africa: the view from Wadh Lang'o, Nyanza Province, Western Kenya

Abstract: The site of Wadh Lang'o in southern Nyanza Province (Kenya) has produced a very large faunal assemblage in association with Kansyore, Elmenteitan and Urewe ceramics. The stratigraphy of the site appears to be intact and six dates have been obtained from the sequence, making this the best opportunity to look at diachronic change in subsistence strategies in this region. The main results of the zooarchaeological analysis are presented here, with emphasis on the Kansyore component. Two important findings are disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 40 publications
(72 reference statements)
0
46
0
Order By: Relevance
“…2), it was also likely situated in a grassy environment. Fishing is a significant activity at both sites; however, the mammals in the Elmenteitan faunal horizons in Trench 1, Wadh Lang'o (below datum 140-190 cm), are predominantly (89-91%) domestic, suggesting limited hunting (75). Alcelaphines are represented, but the zebra and oribi present at Gogo Falls are absent at Wadh Lang'o.…”
Section: Bos Taurus (5)mentioning
confidence: 99%
See 1 more Smart Citation
“…2), it was also likely situated in a grassy environment. Fishing is a significant activity at both sites; however, the mammals in the Elmenteitan faunal horizons in Trench 1, Wadh Lang'o (below datum 140-190 cm), are predominantly (89-91%) domestic, suggesting limited hunting (75). Alcelaphines are represented, but the zebra and oribi present at Gogo Falls are absent at Wadh Lang'o.…”
Section: Bos Taurus (5)mentioning
confidence: 99%
“…Recent research in the Lake Victoria basin has shown that the nearby site of Wadh Lang'o shares similar dates of 1,950 ± 35 y B.P. for early Elmenteitan levels (27,75) and a number of similarities with Gogo Falls: Wadh Lang'o is also a large open-air site with a long sequence containing Kansyore, Elmenteitan, and Iron Age horizons (27,75). It is situated in a similar environmental setting, on the banks of a river flowing into Lake Victoria.…”
Section: Bos Taurus (5)mentioning
confidence: 99%
“…As Dale and Ashley mention earlier in this volume, radiocarbon dates were erroneous but the Kansyore component likely dates to the early Kansyore phase, based on material analogies with dated contexts at the nearby Pundo shell midden and the more distant open-air site of Siror. A few teeth likely belonging to domestic caprines were found among the wild faunal remains, suggesting that there might be also later Kansyore influence at the site, since domesticates have not been recovered at any early Kansyore sites (Lane et al 2007;Prendergast 2010).…”
Section: Sites Under Studymentioning
confidence: 94%
“…The earliest known ceramic type in eastern Africa, Kansyore pottery, dates to between c. 8000 and c. 2000 BP and is associated with a delayed-return hunter-gatherer economy focused on aquatic resources (Karega-Mũnene 2002; Dale et al 2004;Dale and Ashley 2010;Prendergast 2010). Sites are found across a wide region that incorporates western Kenya, northern Tanzania and southern Uganda, with a possible local variant, Lokabulo, found in South Sudan (see Figure 1).…”
Section: Ceramic Studies In the Great Lakes And Rift Valleymentioning
confidence: 99%
“…A bimodal distribution of sites between riverine and lacustrine locations has long been proposed, with Robertshaw (1991) suggesting that both were 'magnet locations' because of their abundant aquatic resources. More recently, Prendergast (2010) and Prendergast and Lane (2010) have argued that this distinctive spatial pattern represents seasonal occupation. Riverine sites are thought to have been chosen for the wet season, when fish were spawning up the rapids, while during the leaner dry season lacustrine shores provided temporary accommodation with access to both shellfish and species such as lungfish (Protopterus aethiopicus), which aestivate in the shallow reeds (see also Seitsonen 2010 for supporting evidence from an an analysis of associated lithic assemblages).…”
Section: Kansyore Ceramics Research Backgroundmentioning
confidence: 99%